(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Ingliz tilida qo‘shimcha fe’lga qo‘shilganda ish-harakatning qachon, qayerda, qanday tartibda bajarilishini ifodalaydi, shunday qilib ergash gap gapga aylanadi: My friend speaks English well (My brother speaks English well). Ana shu xususiyatiga ko‘ra ravish maqom ifodalovchi so‘zlar turkumiga kirishi mumkin. In English, when an adverb is attached to a verb, it expresses when, where, and in what order the action is performed, thus the adverb becomes a sentence: My friend speaks English well (My brother speaks English well). Due to this feature, ravish can be included in the group of words expressing status.